2007
DOI: 10.1177/1046878107300670
|View full text |Cite
|
Sign up to set email alerts
|

An evolving simulation/gaming process to facilitate adaptive watershed management in northern mountainous Thailand

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 9 publications
2
24
0
3
Order By: Relevance
“…The RPG and MAS model used in the previous cycle were modified to conceive a new set of RPG and MAS model adjusted to the villagers' socio-economic preoccupations. A detailed description of the way the RPG and MAS models were adjusted is available in (Barnaud et al 2007a). Both tools were used with villagers during a three day long participatory modelling and simulation workshop held in the village school.…”
Section: Methodology Used In the Second Commod Cycle Focusing On Creditmentioning
confidence: 99%
“…The RPG and MAS model used in the previous cycle were modified to conceive a new set of RPG and MAS model adjusted to the villagers' socio-economic preoccupations. A detailed description of the way the RPG and MAS models were adjusted is available in (Barnaud et al 2007a). Both tools were used with villagers during a three day long participatory modelling and simulation workshop held in the village school.…”
Section: Methodology Used In the Second Commod Cycle Focusing On Creditmentioning
confidence: 99%
“…Within advocates of local participatory processes, some cast doubts about those supposedly participatory approaches that end up empowering the already powerful (Rudqvist and Woodford-Berger 1996;Barnaud et al 2007). Participatory role playing game designers are keen to avoid such situations (Barnaud et al 2007) by trying to make them instruments that effectively promote inclusion, communication, reflection and social learning among stakeholders in conflict.…”
Section: Discussionmentioning
confidence: 99%
“…Barnaud et al 2007;Sandkler et al 2010) expect an increasing need for landscape-level cooperation and coordination in order to strengthen adaptive co-management and governance of social-environmental processes. While developing more sophisticated RPGs and scenario simulators, we have continued to find SS to be both a promising research tool and a good introduction to coordination dilemmas and strategies for those stakeholders involved in building and/or using more realistic role playing games in the context of participatory rural land use planning.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the presence of a fishery creates a reciprocal dependence -the order of access to fish is the opposite of the order of access to water -that increases the resilience of the decentralized solution. Some researchers have also built ABMs collaboratively with those being modelled, as a means of facilitating cooperation and resource sharing (Barnaud et al 2007;Naivinit et al 2010;Barnaud et al 2006).…”
Section: Agent-based Modellingmentioning
confidence: 99%
“…The IDT approach departs from companion modelling style approaches, where the model is built through an interactive process involving the stakeholders that the model represents (Barnaud et al 2007;Gurung et al 2006;Naivinit et al 2010;Naivinit et al 2008;Hoanh et al 2008). Companion modelling exercises are typically undertaken to facilitate shared learning and enhance cooperation that can address existing conflicts.…”
Section: Games and Educationmentioning
confidence: 99%